R&D investment, financial and environmental performance nexuses via bootstrap fourier quantiles granger causality test - Feng-Li Lin (Economies, 2021)
This study investigated the relationship between R&D investments and financial and environmental performance. The direction, size, and significance of various phases of these variables were generated using the bootstrap Fourier quantiles Granger causality test. In our results, a positive relationship between R&D investment and CO2 emission reductions was found at two tails of quantiles. Additionally, we observed a significantly positive relationship between financial performance and CO2 emission reductions at the 0.5 quantile and above. The correlation between R&D investment and financial performance was identified to be positive under the 0.3, 0.4, 0.5 and 0.9 quantiles and negative under the 0.5 and 0.6 quantiles. The changing linkages among R&D investment, environmental performance and financial performance found in this study provide important information for policy makers, aiding in the development of R&D strategies to upgrade financial and environmental performance simultaneously.
Keywords: 330; bootstrap Fourier quantiles Granger causality test; environmental performance; financial performance; R&D